1995
DOI: 10.1002/art.1780380117
|View full text |Cite
|
Sign up to set email alerts
|

Mannose-binding protein gene polymorphism in systemic lupus erythematosus

Abstract: Objective. To determine whether an allelic form of mannose-binding protein (MBP) incapable of activating complement is associated with susceptibility to systemic lupus erythematosus (SLE).Methods. MBP allele frequencies were determined by amplification refractory mutation systempolymerase chain reaction in 102 white SLE patients and 136 controls.Results. The MBP allele that is unable to activate complement was present in 42 SLE patients ( Conclusion. Our results suggest that this allele of the MBP gene repres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
84
1
3

Year Published

1995
1995
2005
2005

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 150 publications
(92 citation statements)
references
References 28 publications
3
84
1
3
Order By: Relevance
“…Furthermore, SPD null animals have defective in vivo clearance of apoptotic cells in the lung (14). These observations suggest that MBL could also have a role in apoptotic cell clearance in vivo and, along with the reports of increased risk of autoimmunity in MBL low individuals (6,7), have raised the question of whether lack of MBL might result in autoimmunity as is observed with C1q deficiency (15). To study the role of MBL in vivo, we have generated mice deficient in both genes encoding mouse MBL (MBLA and MBLC) (3), and here we report the role of MBL in autoimmunity.…”
mentioning
confidence: 69%
See 1 more Smart Citation
“…Furthermore, SPD null animals have defective in vivo clearance of apoptotic cells in the lung (14). These observations suggest that MBL could also have a role in apoptotic cell clearance in vivo and, along with the reports of increased risk of autoimmunity in MBL low individuals (6,7), have raised the question of whether lack of MBL might result in autoimmunity as is observed with C1q deficiency (15). To study the role of MBL in vivo, we have generated mice deficient in both genes encoding mouse MBL (MBLA and MBLC) (3), and here we report the role of MBL in autoimmunity.…”
mentioning
confidence: 69%
“…Defects in the first component of complement are strongly associated with autoimmunity such that Ͼ95% of patients deficient in C1q develop a systemic autoimmune syndrome (5). In addition, MBL haplotypes that specify low levels of an aberrant form of MBL unable to activate complement are also reported to be associated with a low but increased risk of autoimmunity (6,7). Apoptotic cells have been shown to be a preferential source of many autoantigens (8) and failure to promptly remove dying cells has been implicated in the pathogenesis of systemic lupus erythematosus (5, 9, 10), a prototypic autoimmune disease.…”
mentioning
confidence: 99%
“…It also interacts with viral envelopes containing mannose protein, such as the immunodeficiency virus [58]. One particular allele of the MBP gene, which is unable to activate the classical pathway of the complement, has shown a moderate association with SLE in two different ethnic populations [59,60].…”
Section: Studies Of Candidate Genesmentioning
confidence: 99%
“…In the study of 102 SLE patients in the UK, and 111 Chinese SLE patients in Hong Kong, there was a modest but statistically not significant increase in the frequency of G54D mutation (0.25 in SLE patients vs 0.19 in controls; odds ratio 1.5 and 0.17 in SLE patients vs 0.11 in controls; odds ratio 1.7). 10,12 In the 50 Spanish SLE patients, a significant increase in the G54D frequency (0.28 in SLE patients vs 0.16 in controls) has been reported. 11 However, the allele frequency of G54D mutation in our 95 SLE patients was 0.226 that was comparable to the frequency of 0.233 in controls.…”
mentioning
confidence: 96%
“…Studies in the UK and Spanish populations, as well as in Hong Kong Chinese have suggested the association of MBL deficiency with systemic lupus erythematosus (SLE). [10][11][12] In the case of rheumatoid arthritis (RA), results are controversial. Presence 13 or absence 14,15 of association of MBL deficiency with RA have been reported.…”
mentioning
confidence: 99%